Gastric Endocrine Cell Carcinoma Coexistent with Adenocarcinoma - Nobuhiro Takeuchi; Nomura Yusuke; Tetsuo Maeda; Kazuyoshi Naba (Case Reports in Medicine)
A 69-year-old female presented to our institution with epigastralgia and abdominal distension. Upper gastrointestinal series revealed a 5 cm ulcerative lesion with irregular margins and elevated distinct borders from the angle to the pyloric ring. Gastroendoscopy revealed a Borrmann type 2 tumor. Several biopsied specimens revealed proliferation of small and heterogeneous cancer cells with rich chromatin and fibrous septum with rich vessels at connective tissues, which was confirmed as gastric endocrine cell carcinoma (ECC) on immunostaining with chromogranin and synaptophysin. Furthermore, other specimens revealed atypical cells forming glandular structures, which were confirmed as well-differentiated tubular adenocarcinomas. Distal gastrectomy with D2 lymph node dissection and Billroth I reconstruction was performed. Pathological examination of the gross specimen revealed that adenocarcinoma comprised <10% of all cancer cells. Close analysis of ECC revealed a mixture of small and large cells. According to the WHO 2010 classification of gastrointestinal neuroendocrine tumors, this gastric tumor was diagnosed as neuroendocrine carcinoma. The patient was administered adjuvant chemotherapy with cisplatin and etoposide. One year following surgery, follow-up abdominal CT revealed multiple liver metastases. The patient received the best supportive care but eventually died 18 months after surgery. Here we present this case of gastric ECC coexistent with adenocarcinoma.